3D numerical simulation of condensation and condensate behaviors on textured structures using lattice Boltzmann method. (October 2020) - Li, Mingjie; Qu, Jingguo; Ocłoń, Pawel; Wei, Jinjia; Tao, Wenquan
Highlights: Nucleation position rises from bottom to top with the increase of surface hydrophobicity. For C3 the condensation mode transits from dropwise to film condensation. Cases with hybrid surface have shorter nucleation time than homogeneous surfaces. Hydrophilic spots on hydrophobic pillars can shorten nucleation time and increase heat flux. Abstract: Condensation is one of the most widely investigated interface phenomenon in science and engineering. However the three-dimensional (3D) condensate behaviors including the initial nucleation, growth, coalescence, penetration, spreading or expansion on textured surfaces have seldom been clarified comprehensively. In this work, the 3D pseudopotential LB model with a phase change model is employed, and the condensation process on textured structures with homogeneous and inhomogeneous wettability is investigated. It is found that the nucleation position rises to the top of the structure and the nucleation time gets longer with the increase of surface hydrophobicity when condensation occurs on homogeneous textured structure, and the dropwise condensation mode transits into the film condensation. The condensation on structures with inhomogeneous surface wettability at the top, side and bottom of the pillars and structures with hybrid top (namely hydrophilic spots in the center of the top of the hydrophobic pillars) is then investigated. It is concluded that hybrid top of the textured structures can enhance condensation heat transfer, shorten the nucleation time, and at the same time maintain the condensate in the Cassie state for a long time before the condensation mode transition, leading to the best condensation performance.